Gestão de recursos pesqueiros na RESEX Mãe Grande de Curuçá: comunidade de Arapiranga de Dentro - CRUZ, Mariana Neves (Universidade Federal do Pará, 2017)
This issue is about the co- management of the fishery resources in Protected Areas, emphasizing the RESEX Mãe Grande de Curuçá. Through the case of the community of Arapiranga de Dentro, this study aims to analysis how the management of the fishery resources are affected by this kind of government strategy. This study was made by bibliographical survey about the themes: Territory, Artisanal Fishery and Common Uses Resources. The qualitative research was made by Field work, semi – structured questionnaires application. Two sketches and maps were build aims to show the fishery use area of the community of Arapiranga. This study intends to analyze not only the Legal aspect of the protected areas but also how the specific Legislation are absorbed and inserted by the using population and how the local practices of resources extraction are affected by this kind of intermediation relation of the territory – population – resource.